Fiscal Reforms in Low-Income Countries - Clements, Benedict (Occasional Papers; Occasional Paper ;, 1998)
The reform of fiscal policies and institutions lies at the heart of structural adjustment in developing countries. Although the immediate aim of such reform is to reduce fiscal imbalances to achieve macroeconomic stability, the long-term goal is to secure more durable improvements in fiscal performance. This study reviews the fiscal reform experience of 36 low-income developing countries that undertook macroeconomic and structural adjustment in the context of the IMF's Structural Adjustment Facility and Enhanced Structural Adjustment Facility during the period of 1985-95.